MEMAHAMI KONSEP KEMANUNGGALAN DALAM AKUNTANSI: KRITIK ATAS UPAYA MENDEKONSTRUKSI AKUNTANSI KONVENSIONAL MENUJU AKUNTANSI SYARIAH DALAM BINGKAI TASAWUF - Agung Budi Sulistiyo (Universitas Jember, 2010)
Until now, have not many Shari’ah accounting researchers and thinkers who perform critical review of the various Shari’ah accounting concepts. This paper done in order to view critically one of Shari’ah accounting concepts, that is manunggaling kawulo gusti. This concepts is to symbolize or representate of the pairs of epistemology. This symbolizasion is not precise because of these two things have difference understanding. The pairs of epistemology to point out combinationfrom two differences characteristic, but have same level whereas manunggaling kawulo gusti need to united and disolved from these two differences characteristic and level. Because of that, in principle to describe reality of accountancy that holistic characteristic,we must give two characteristic like egoistic-altruistic, masculine-feminin, materialistic-spiritualistic etc in same level and isn’t disolved each other to or change one of other. Keywords: syari’ah accounting, pairs of epistemology, manunggaling kawulo gusti